COMPARISON OF PHYSICAL ACTIVITY LEVEL AND FOOD ADDICTION OF PHYSICAL EDUCATION AND SPORTS SCIENCE COLLEGE STUDENTS - KAYHAN, Mert; ÜNVEREN, Alparslan (Sportif Bakış: Spor ve Eğitim Bilimleri Dergisi, 2017)
The aim of this study is to examine the physical activity level and food addiction of physical education and sport science students and to investigate the excessive food consumption. In the study in order to evaluate food addiction of students “Yale Food Addiction Scale” which was developed by Gearhardt et al. (2009) and adapted to Turkish by Bayraktar et al. (2012) were used as data gathering tools. Besides, in order to evaluate physical activity level of students “International Physical Activity Questionnaire” which was developed by Craig et al. (2003) and adapted to Turkish by Ozturk (2005) were used as data gathering tools. The information obtained as a result of the research was analyzed with the IBM SPSS statistics 23. According to the result of Yale Food Addiction Scale, 290 out of a total of 383 subjects who participated in the study met the diagnosis of food addiction. In addition, the most preferred food by students from the list of foods that problem from excessive food consumption was wafer/chocolate with 44.9%, the second one was 32.6% cola/soda, and 28.7% with chips in third. Food addiction has been observed in the majority of participants.